THE NATIONAL-CULTURAL COMPONENT IN THE PHRASEOLOGISMS OF THE WORKS OF TROKHYM ZINKIVSKY - Shkola, Galyna; Pashynska, Liudmyla (Linguistic Bulletin (Movoznavchyi Visnyk), 2023)
Introduction. The article is devoted to the study of phrasemics with a national-cultural component in the works of Trokhym Zinkivskyi. Purpose – to find out the peculiarities of the use of phraseological units with a national-cultural component in the works of T. Zinkivskyi. The research material is phraseological units selected from poetic, prose, lyrical-epic, dramatic texts and the writer’s epistolary. Methods. The selected factual material was processed using the descriptive method, which provided for the identification and systematization of phraseological units, and the component method, which enabled their structural and semantic analysis. Results. Expressiveness is given to the language of T. Zinkivskyi’s works by numerous phraseological units that reflect the worldview not only of the characters, but also of the author himself. The article found out that the writer uses stable sayings of book origin and phraseology of oral conversation. Among the book phrases, biblicalisms are singled out. The author most actively introduces vernacular phraseological turns into his works to denote the historical past of the Ukrainian people, interpersonal relationships, human character traits, and everyday objects. In order to update the semantics and structure of phraseological units, T. Zinkivskyi resorts to phrase transformations: replacement of component(s) of a phraseological unit, ellipsis, contamination. Phraseologisms of T. Zinkivskyi’s works can be combined into synonymous series and antonymous pairs. Conclusion. Phraseology reflects the traditions, customs, mythological and religious ideas of the people, its history and daily life. The article elucidates the national and cultural semantics of phraseological units in the artistic and epistolary speech of the Ukrainian writer of the second half of the 19th century, Trokhym Zinkivskyi. Phraseological units strengthen the expressiveness of the statement, make the language of the author’s works concise, dynamic, and stylistically expressive.